Transcriptomic meta-analysis and functional validation identify genes linked to adaptation and involved in high-light acclimation in Synechocystis sp. PCC 6803 - Abdel-Salam, Eslam M.; Figueroa-Gonzalez, Theo; Leister, Dario (Frontiers in Photobiology, 2023)
Several mechanisms of high light (HL) acclimation have been identified in Synechocystis sp. PCC 6803. However, there are still gaps in understanding of the complex regulatory networks and molecular interactions involved. This study aims to investigate the molecular mechanisms underlying HL acclimation in Synechocystis by performing a meta-analysis of transcriptomic data. A total of 411 differentially expressed genes (DEGs) were identified in the meta-analysis, of which 179 were unique to the meta-analysis. These findings indicate a coordinated response of the Synechocystis transcriptome to HL, with specific genes being activated or suppressed to cope with the challenging conditions. Of all the DEGs, 307 were related to primary metabolism, 52 were involved in photosynthesis and light-harvesting processes, and 52 genes had no known function or were not properly annotated. Gene ontology and KEGG pathway enrichment analyses revealed the involvement of DEGs in various biological processes and pathways, including photosynthesis, energy metabolism and oxidative stress response. Comparison with previous HL adaptive laboratory evolution (ALE) experiments revealed 17 DEGs that had acquired adaptive mutations after HL ALE. Three of these adaptive mutations which lead to amino acid exchanges in the corresponding proteins (sll0267L1189P, sll0355F254S, and slr1855D200G) were selected to test their impact on HL acclimation in Synechocystis. The laboratory validation of strains carrying these three mutations, showed that each mutation had a positive effect on HL acclimation when reconstructed in the Synechocystis laboratory type (LT) background. The three mutants reached higher cell densities at the end of cultivation, showed comparable levels of chlorophyll fluorescence when exposed to incremental red-orange light, and at least one of the three mutations may alter gene function rather than suppress it. These findings offer valuable insight into the HL acclimation and adaptation of Synechocystis and contribute to a more comprehensive understanding of the molecular mechanisms that underlie its adaptation to HL. These results may direct future studies seeking to enhance the adaptability of cyanobacteria and related species to HL.